2014
DOI: 10.1007/s10681-014-1129-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in root mass of Lolium perenne varieties under field conditions

Abstract: Although grasses have dense rooting systems, nutrient uptake and productivity can be increased, and N-leaching reduced, if rooting is further improved. The variation in root mass of 16 varieties of Lolium perenne was studied under field conditions in two experiments on sandy soil in The Netherlands. The chosen varieties differed in genetic and aboveground characteristics such as ploidy, productivity and grass cover. Root dry matter (RDM) was measured in the 0-8, 8-16 and 16-24 cm soil layers. In summary, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This may indicate that species with higher SRL are better accustomed to retrieving P in a P‐limiting environment. Many studies have reported differences in rooting depth, SRL and other root morphological traits among grass species and cultivars ( e.g ., Crush et al, ; Deru et al, ). These characteristics may change with the presence or absence of P fertilization ( Hill et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that species with higher SRL are better accustomed to retrieving P in a P‐limiting environment. Many studies have reported differences in rooting depth, SRL and other root morphological traits among grass species and cultivars ( e.g ., Crush et al, ; Deru et al, ). These characteristics may change with the presence or absence of P fertilization ( Hill et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tetraploid cultivar Calibra had higher values upon storage at all temperatures except at the room temperature (p<0.01). Deru et al (2014), in two field trials, identified different effect of ploidy level to the perennial ryegrass root dry matter mass and length. The greatest differences in root weight between cultivars were observed upon the storage at -20 C (4.28 g) and least upon 10 C (0.64 g).…”
Section: Resultsmentioning
confidence: 96%
“…For RDW, genotypes showed similar behavior up to 60 DAE, while in the other evaluation times, tetraploid ryegrass showed higher accumulation; at 120 DAE, the value was 45% higher than that of diploid ryegrass, with 39.78 g per plant ( Figure 2D). Tetraploid ryegrass plants have a more developed root system, contributing to efficient use of water and assimilation of limited nutrients in the environment, reducing soil erosion and improving soil biological characteristics due to the increased carbon and other nutrients source (Deru et al, 2014).…”
Section: Fitness Costmentioning
confidence: 99%